Geopolitical scenario of the ASEAN region andimplications for international relations / Qasim Ahmad - Ahmad, Qasim (Universiti Teknologi MARA, Shah Alam, 2005)
ASEAN was founded in 1967 as a five member economic regional grouping. At that time the Cold War, or its very manifestation, was raging at ASEAN's very doorstep. But ASEAN had always wanted to play down any political aspect of the organization. This political restrain was so designed because the founding members (Indonesia, Malaysia, the Philippines, Singapore and Thailand) 'did not want ASEAN to be mistaken for a military grouping among political allies - as some of its predecessors had been.